Pembuatan Iklan Marketing Interior Rumah Menggunakan Sketchup 3D Berbasis Panorama 360 - Achmad Rizky Fazar; Ari Usman; Arief Budiman (LKP Unity Academy, 2023)
In today's computer technology is growing very rapidly, and can be used as a solution to convey or provide information. One of the computer technology to convey information is media promotion. At this time in advertising the house can use video or other media. Here the ads used are marketing ads. As time goes on, in home marketing advertising is also growing. Therefore, the researcher will create a house marketing advertisement based on 360 panoramas, and make a house design using 3D sketchup. For the creation of 360 panoramas using a website-based application called theasys – 360 VR Online. The purpose of the researcher making this research is to help home developers in advertising a house and home developers don't need to make sample houses anymore.